2022
DOI: 10.21203/rs.3.rs-1385131/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting Hip-Knee-Ankle and Femorotibial Angles from Knee Radiographs with Deep Learning

Abstract: Knee alignment affects the development and surgical treatment of knee osteoarthritis. This research aimed to improve its automatic measurement from posteroanterior (PA) knee radiographs by using convolutional neural networks. Radiographs from the Osteoarthritis Initiative with corresponding femorotibial angle (FTA, N = 6149) and hip-knee-ankle angle (HKA, N = 2351) measurements, were split into training, validation, and test datasets in a 70:15:15 ratio. Separate models were developed for the prediction of FTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…CNNs achieved prediction accuracies of 88.2% and 86.3% for femoral components and tibial components, respectively [19]. In another study CNNs, trained on 6,149 radiographs, reported a mean absolute error of 0.8 • on femoratibial angle prediction [20]. In another study on 1,842 knees X-ray images, the error obtained by CNNs on hinge point, surgical point, and Fujisawa point was, respectively 2.06±1.16 mm, 2.71±1.45 mm, and 2.01±1.30 mm [30].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…CNNs achieved prediction accuracies of 88.2% and 86.3% for femoral components and tibial components, respectively [19]. In another study CNNs, trained on 6,149 radiographs, reported a mean absolute error of 0.8 • on femoratibial angle prediction [20]. In another study on 1,842 knees X-ray images, the error obtained by CNNs on hinge point, surgical point, and Fujisawa point was, respectively 2.06±1.16 mm, 2.71±1.45 mm, and 2.01±1.30 mm [30].…”
Section: Discussionmentioning
confidence: 98%
“…Concurrently with the emergence of MR technologies, there have been substantial advances in artificial intelligence (AI) tools, such as convolutional neural networks (CNN), that showcased the potential of greatly automatizing image processing in many different clinical applications, for diagnostic and surgical planning purposes [13]. In orthopedics, CNN models were applied for the segmentation of knee bones and cartilage from magnetic resonance imaging providing invaluable support in the diagnosis of osteoarthritis [14], [15], for the automatic segmentation of bones in knee CT scans for the realization of personalized cutting guides [7], [16], [17], for total knee arthroplasty planning using X-ray radiographs [18]- [20]. Some initial studies have explored the potential of integrating AI tools with technologies for extended reality in hip and knee arthroplasty [21].…”
Section: Introductionmentioning
confidence: 99%